Innate Immunity in pathogenesis of Tuberculosis: An Overview: Exploring the early interactions between Mycobacterium tuberculosis and innate immune cells (Journal of Advances and Scholarly Researches in Allied Education, 2022)
An evolutionary conserved mechanism that detects and fights off illness and discomfort is theinnate immune system. Through a variety of germline-encoded cell surface or cytoplasmic receptors,innate immune signalling rapidly detects infectious threats and delivers signals for the application ofappropriate defences through adaptors, kinases, and transcription factors, leading to the generation ofcytokines. Inflammatory reactions, which are the innate immune system's initial response to pathogenicsignals, must be quick and focused in order to create a physical barrier against the spread of infectionand must then be stopped once the pathogens have been eradicated.The human pathogen Mycobacterium tuberculosis, which largely attacks innate immune cells patrollingthe lung, is what causes tuberculosis (TB). By identifying the inflammatory environment in the lungs andencouraging the development of adaptive immune responses, innate immune cells act as barometers ofthe immune response against Mycobacterium tuberculosisinfection. However, M. tb can easily controlinnate immune cells, which are also potential habitats for bacterial proliferation. Particularly in thecontext of human infection, our knowledge of the early interactions between M. tb and innate immunecells is restricted. This review will concentrate on innate immune pathways discovered through humanimmunogenic research.